Proposta de melhoria da qualidade de vida no trabalho dos funcionários da pró-reitoria de ensino de um instituto federal de educação da região norte do Brasil através de intervenção ergonômica - Araújo, Márcio de Lima (2025)
Ergonomic intervention is essential to promote workers' health, well-being, and quality of life by adapting the environment and tasks to their physical and cognitive capabilities, preventing occupational illnesses, and increasing productivity. With this in mind, the objective of this study was to analyze the work environment of the vicerectorate of education at a federal educational institution in northern Brazil and propose ergonomic adjustments that could contribute to improving the quality of life of its employees. To this end, an ergonomic intervention was carried out using research instruments such as the RULA, OWAS, sociodemographic, and IAPT questionnaires, in addition to measuring environmental factors related to heat stress, noise, and illuminance, and comparing the data obtained with those recommended in current regulatory standards. The results showed that the ergonomic conditions of the work environment require attention. Employees, in general, are not productive, some work conditions require adaptations, and some structural conditions of the environment need to be reviewed. Suggestions were proposed that can contribute to improving ergonomic working conditions and, consequently, the quality of life of workers.